Development of interactive e-book for science learning in fifth grade elementary school students - Khofifah, Imroatul; Meirza Nanda Faradita; Fajar Setiawan (JURNAL PENDIDIKAN DASAR NUSANTARA, 2023)
The type of research used by the researchers is generally aimed at developing a learning media or improving existing products to make them more effective. This study is development research, specifically focusing on the development of an interactive E-book-based media for Science learning in fifth-grade elementary school students, specifically covering the topic of the human movement organ. The method employed in this research is Research and Development (RnD), using the 4-D Thiagarajan model (Definition, Design, Development, Dissemination). The research instruments used include Validation Sheets (media experts and subject matter experts), Questionnaires (student responses), and Test Sheets (Learning Outcome Tests). The study results in the creation of an electronic medium, an interactive E-book, that completed high-quality criteria in terms of validity, practicality, and effectiveness. The media's validation results by the subject matter experts were 87.5%, and by the media experts were 86.5%, both categorized as "Highly Feasible." The practicality of the media was rated at 92.2% with the criterion of "Practical" based on student learning outcomes. The effectiveness test showed that 87% of students achieved scores that completed the Minimum Mastery Criteria (KKM). In conclusion, the developed product obtained high-quality criteria in terms of suitability, practicality, and effectiveness.